2015
DOI: 10.1039/c5ra11136f
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic application of SO42−/Fe–ZrO2nanoparticles synthesized by a urea hydrolysis method for environmentally benign one pot synthesis of 1,8-dioxodecahydroacridines

Abstract: A series of Fe 2 O 3 -ZrO 2 mixed oxides (FexZr) were prepared by colloidal precipitation method using urea as mild hydrolyzing agent. The sulfate ions were grafted onto the surface of the mixed oxide by treatment with dilute sulfuric acid and subsequent thermal activation. The resulting sulfated grafted mixed oxides (SFexZr) were characterized using XRD, FTIR, Raman, surface area measurement, UV-Vis, XPS, TPD, FESEM and HRTEM techniques. XRD study indicated formation of a substitutional type solid solution in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 62 publications
(130 reference statements)
0
8
0
Order By: Relevance
“…ZrO 2 is a direct band gap insulator which shows an interband transition in the UV region of the spectrum. [41][42][43] The monoclinic form of ZrO 2 has two direct interband transitions at 5.93 and 5.17 eV, whereas the tetragonal form has a band gap of 5.1 eV. 41 In the present case, the peak at 214 nm can be assigned to the O 2− → Zr 4+ charge transfer transition arising from the host zirconia matrix (figure 6 I).…”
Section: Characterization Of the Ba/zro 2 Nanoparticlesmentioning
confidence: 55%
See 3 more Smart Citations
“…ZrO 2 is a direct band gap insulator which shows an interband transition in the UV region of the spectrum. [41][42][43] The monoclinic form of ZrO 2 has two direct interband transitions at 5.93 and 5.17 eV, whereas the tetragonal form has a band gap of 5.1 eV. 41 In the present case, the peak at 214 nm can be assigned to the O 2− → Zr 4+ charge transfer transition arising from the host zirconia matrix (figure 6 I).…”
Section: Characterization Of the Ba/zro 2 Nanoparticlesmentioning
confidence: 55%
“…The stabilization of the tetragonal phase in zirconia sample has been a subject of intense study in literature. [38][39][40][41][42][43] The tetragonal phase being metastable in nature undergoes a martensitic transformation to the monoclinic phase. 41 The presence of aliovalent impurities in zirconia structure as well as surface modification by ionic species selectively stabilizes the tetragonal phase.…”
Section: Characterization Of the Ba/zro 2 Nanoparticlesmentioning
confidence: 99%
See 2 more Smart Citations
“…[92] Simple technique, green reaction media, diverse functional utility, magnetically recovered and reusable catalyst are the additional advantages of the present methodology [Scheme 11, Method 3]. Pradhan and Mishra [93] synthesized SO 4 2À /Fe-ZrO 2 nanoparticles using colloidal precipitation method, where sulfate ions were fabricated on the surface of mixed oxides and further studied their catalytic efficiency on acridinediones synthesis using MeCN solvent. The authors also evaluated the effect of Fe Firstly, Rahmani and coauthors [94] demonstrated the applicability of nano titanium dioxide as an proficient and recyclable heterogenous catalyst for the synthesis of variety of 1,8dioxodecahydroacridines in excellent yields via simple procedure [Scheme 12, Method 1].…”
Section: Nano-catalyzed Synthesismentioning
confidence: 99%